2020
DOI: 10.1177/1035304619899770
|View full text |Cite
|
Sign up to set email alerts
|

Commuting time and sickness absence in China: Rural/urban variations and Hukou impacts

Abstract: This article addresses three main issues: the relationship between commute time and sickness absence, the heterogeneity of the commuting–absenteeism effect between rural migrants and urban citizens, and the effect of China’s Hukou system on the commuting–absenteeism effect. It applies a unique set of employer–employee matched data in China and a zero-inflated negative binomial model. We find clear evidence that a longer commuting time contributes to an increase in sickness absence. The heterogeneity of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Furthermore, research elsewhere has shown that increased sickness absences are associated with longer commuting times [24,25], and longer commuting distances [26].…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…Furthermore, research elsewhere has shown that increased sickness absences are associated with longer commuting times [24,25], and longer commuting distances [26].…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…Previous studies on the physical and psychological health of workers have largely focused on the separate impacts of commuting time, work stress, and physical exercise on employees’ health ( M. Guo et al, 2020 ; Sha et al, 2019a ; Sun et al, 2020 ; Xu et al, 2017 ). Less attention has been paid to the interaction of all three and to the impact of physical exercise on commuting time.…”
Section: Discussionmentioning
confidence: 99%
“…Commuting time and traffic congestion have become significant factors affecting people’s physical and mental well-being ( Dickerson et al, 2014 ; Xu et al, 2013 ). Longer commutes have a positive effect on employees’ absenteeism due to illness ( M. Guo et al, 2020 ). Hansson et al (2011) found that there is a relationship between public transport commuting time and negative health outcomes.…”
mentioning
confidence: 99%
See 2 more Smart Citations